تكنولوجيا المعلومات والاتصال ومساهمتها في تحسين فعالية اتخاذ القرارات الادارية - دراسة حالة مؤسسة اتصالات الجزائر وكالة الوادي - - عبدالعالي, قدور; الطاهر, بن السايح (جامعة الوادي - University of Eloued, 2023)
" تناولت هذه الدراسة موضوع تكنولوجيا المعلومات والإتصال ومساهمتها في تحسين اتخاذ القرارات الإدارية - دراسة حالة مؤسسة اتصالات الجزائر- حيث هدفت إلى تأكيد دور تكنولوجيا المعلومات والاتصال في تحسين اتخاذ القرارات الإدارية وكشف عن العلاقة بين تكنولوجيا المعلومات والاتصال اتخاذ القرار حيث استهدفت الدراسة (34 ) عامل بالمؤسسة بمختلف مراتبهم يعملون في مناصب متعددة حيث جمعت البيانات عن طريق تصميم استبيان خصص جزء منه تكنولوجيا المعلومات والاتصال وتكونت على محاور جزء مخصص للمتغير المستقل و جزء مخصص لمتغير التابع وهو فعالية القرارات الإدارية فقد تضمن 14 عبارة تتعلق بالموضوع. وقد اعتمدنا في التحليل على أسلوب التحليل الإحصائي ، والتكرار والنسب والمتوسط الحسابي،بالإضافة إلى الانحراف المعياري . كذلك أيضا استخدما بعض من الساليب الاستدلالية المتمثلة في: معامل الثبات ألفا كرونباخ معامل الارتباط بيرسون. وقد خلصت الدراسة الى مجموعة من النتائج اهمها وجود اثر ذو دلالة احصائية باستخدام تكنولوجيا المعلومات و الاتصال في تحين فعالية القرارات الادارية"" This study dealt with the topic of information and communication technology and its contribution to improving administrative decision-making - the case study of the Algiers Communications Corporation. It aimed to emphasize the role of ICT in improving management decision-making and revealed the relationship between ICT and decision-making The study targeted (34) employees of the institution in various positions serving in multiple positions. The data were collected through the design of a questionnaire, part of which was devoted to ICT, and formed on the axes of a part dedicated to the independent variable and part dedicated to the variable of the administrative decisions. The 14 included a phrase on the subject. In the analysis, we relied on the method of statistical analysis, repetition, ratios and computational medium, as well as standard deviation. They also used some of the evidentiary methods of: the alpha-kronbach persistence coefficient, the Pearson binding coefficient. It concluded by giving theoretical findings and recommendations to the institution in question and proposing future prospects for the study"
Keywords: تكنولوجيا المعلومات والاتصال ، اتخاذ القرار ، القرارات الادارية; ICT. Decision-making. Administrative decisions